1999
DOI: 10.1203/00006450-199911000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Infection, Fetal Inflammatory Response, and Brain Damage in Very Low Birth Weight Infants

Abstract: Echolucent images (EL) of cerebral white matter, seen on cranial ultrasonographic scans of very low birth weight newborns, predict motor and cognitive limitations. We tested the hypothesis that markers of maternal and feto-placental infection were associated with risks of both early (diagnosed at a median age of 7 d) and late (median age = 21 d) EL in a multi-center cohort of 1078 infants <1500 x g. Maternal infection was indicated by fever, leukocytosis, and receipt of antibiotic; fetoplacental inflammation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
213
2
12

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 372 publications
(231 citation statements)
references
References 61 publications
4
213
2
12
Order By: Relevance
“…Others, however, have reported that chorioamnionitis is an antecedent of echolucency (50). Virtually all placentas and umbilical cords that have fetal vasculitis also have inflammation of the membranes, but only approximately half of placentas with membrane inflammation have fetal vasculitis (21,51). This and other findings have led to our view that fetal vasculitis is an indication of the severity and progression of the inflammatory process that tends to involve the membranes before it involves the chorionic plate and umbilical cord.…”
Section: Discussionmentioning
confidence: 81%
“…Others, however, have reported that chorioamnionitis is an antecedent of echolucency (50). Virtually all placentas and umbilical cords that have fetal vasculitis also have inflammation of the membranes, but only approximately half of placentas with membrane inflammation have fetal vasculitis (21,51). This and other findings have led to our view that fetal vasculitis is an indication of the severity and progression of the inflammatory process that tends to involve the membranes before it involves the chorionic plate and umbilical cord.…”
Section: Discussionmentioning
confidence: 81%
“…13 In clinical studies, antenatal exposure to inflammation has been associated with an increased risk for periventricular leukomalacia and cerebral palsy. [14][15][16] Moreover, neurodevelopmental delay has been linked with previous exposure to chorioamnionitis by some studies, although others have failed to reproduce these findings. 10 Animal experimental evidence.…”
Section: Multiorgan Overviewmentioning
confidence: 83%
“…Our research was motivated by the fact that histologic chorioamnionitis and funisitis has been previously linked with neonatal morbidity in preterm infants (27,28). We have previously shown that proteomic profiling of the AF can rapidly and accurately diagnose intra-amniotic inflammation, and can identify women at risk of premature delivery (14).…”
Section: Discussionmentioning
confidence: 99%